A Three-Dimensional Supramolecular Network Constructed from Ti(III) Doped Doubly Bridged Molecular Ribbons catena-bis(μ-pyrazine-2,3-dicarboxylato-N,O,O')-Titanium(III)0.15zinc(II)0.85 and Hydrated Proton via Hydrogen Bonding - Zhang, Xiao-Li; Zhao, Ying-Zhi; Zhang, Zhu; Shu, Kang-Ying; Chai, Wen-Xiang (Asian Journal of Chemistry, 2014)
In the title TiIII doped ZnII complex, Ti0.15Zn0.85(C6H2N2O4)2[(H3O)1.85.(H2O)0.15] (1), obtained during exploring new photochromic materials based on TiIII/IV ion, the coordination polyanion ribbons constructed by pyrazine-2,3-dicarboxylato (2,3-PZDC) ligands is balanced with the close-by hydronium cations. The asymmetric unit consists of a half metal center (composed of 15 % TiIII and 85 % ZnII) on the symmetry axis, a 2,3-PZDC ligand and one hydronium cation (2.91 H atoms disordered at three sites). The TiIII/ZnII ion is coordinated by four 2,3-PZDC ligands, giving a distorted Ti(Zn)N2O4 octahedral coordination geometry. The 2,3-PZDC ligand adopts a bridged 3-coordinated mode with one N and 2-carboxyl O atoms biting one metal center and the other 3-carboxyl O atom coordinating a adjacent metal. In addition, the connected mode of 2,3-PZDC ligand could append a p-p stacking interaction of two pyrazine within the doubly ribbons and especially append three strong hydrogen bonding interactions with hydronium cations. These hydrogen bonding interactions play a key role not only in the formation of the three-dimensional supramolecular network but also to the good thermal stability of the molecular structure. The optical absorption properties of powder samples of the title compound have also been studied and the colored profile of the sample also confirms the presence of the TiIII ion, just like a sapphire.